Design of antiferroelectric polarization configuration for ultrahigh capacitive energy storage via increasing entropy - Yongxiao Zhou; Tianfu Zhang; Liang Chen; Huifen Yu; Ruiyu Wang; Hao Zhang; Jie Wu; Shiqing Deng; He Qi; Chang Zhou; Jun Chen (Nature Communications)
Abstract Electric field induced antiferroelectric-ferroelectric phase transition is a double-edged sword for energy storage properties, which not only offers a congenital superiority with substantial energy storage density but also poses significant challenges such as large polarization hysteresis and poor efficiency, deteriorating the operation and service life of capacitors. Here, entropy increase effect is utilized to simultaneously break the long-range antiferroelectric order and locally adjust the fourfold commensurate modulated polarization configuration, leading to a breakthrough in the trade-off between recoverable energy storge density (14.8 J cm−3) and efficiency (90.2%) in medium-entropy antiferroelectrics. The embedding of non-polar phase regions in the incommensurate antiferroelectric matrices, revealing as a mixture of commensurate, incommensurate, and relaxor antiferroelectric polarization configurations, contributes to the diffuse antiferroelectric-ferroelectric phase transition, enhanced phase transition electric field, delayed polarization saturation, and efficient recovery of polarization. This work demonstrates that controlling local diverse antiferroelectric polarization configurations by increasing entropy is an effective avenue to develop high-performance energy storage antiferroelectrics, with implications that can be extended to other materials and functionalities.